Evaluating the gear stress of novel reverse rotation bit manual screwdriver design for mini screw implants / Rizki Aldila Umas ... [et al.] - Umas, Rizki Aldila; Supriadi, Sugeng; Whulanza, Yudan; Ahmad Fauzi Hasan, Andi Aditya; Kreshanti, Prasetyanugraheni (Universiti Teknologi MARA, 2021)
One of the problems faced by the screwdrivers used for craniomaxillofacial implant fixation is that the maximum torque required for implant removal is significantly higher than the maximum torque needed for inserting implants. Another problem is that the hand torque produced by a right-handed person is lower in the counterclockwise direction, which is the removal direction for miniscrews. The novel design presented here of a manual screwdriver equipped with an epicyclic gear will produce a reverse bit rotation and provide the mechanical advantage of higher torque output. In this study, simulations were conducted by varying the torque input within the range of 0-1000 Nmm with an applied load in each simulation to be adapted based on the epicyclic gear set. The materials used in this study are AISI 316L and Ti6Al4V. The maximum Von Mises stress value was observed in the sun gear from the second gear set at 522.59 MPa (AISI 316L) and 430.76 MPa (Ti6Al4V) for the maximum torque input, which was followed by the planetary and ring gear from the second gear set and then the planetary gear, ring gear, and sun gear from the first gear set. The total deformation also showed the difference between the two materials; the deformation when using AISI 316L as the material was lower than when using Ti6Al4V